Landscaping digital transformation in academic education programmes within Europe - Musiatowicz-Podbiał, Grażyna; Temple, Lucy; Kleiman, Fernando; Bosoer, Lucía (Conference on Digital Government Research, 2025)
This paper aims to recognize content and trends with topics related to Digital Transformation (DT) in educational offers in Higher Education Institutions (HEI), in four EU countries: Austria, Italy, the Netherlands, and Poland. Research is based on benchmarking, recognizing keywords in courses and programmes offered by European universities. The main findings indicate that DT is an essential element of EU education curricula.. The second observation shows DT education as frequently located at the intersection between technology and society. The third finding demonstrates the growing inclusion of DT topics in non-technical disciplines. This research also has practical implications, as its findings on educational portfolios can be applied globally.